The role of spoken vocabulary knowledge in second language speaking proficiency. Issue 3 (4th May 2023) - Uchihara, Takumi; Clenton, Jon
ABSTRACT: Research has suggested the important role of vocabulary knowledge in second language (L2) speaking proficiency. However, earlier studies tended to disregard the congruence in test format between assessing vocabulary knowledge and speaking skills with the former predominantly measured in written format. The current study measured vocabulary knowledge in spoken format to university students speaking English as an L2, and investigated whether spoken vocabulary knowledge predicts speaking proficiency. Forty-six university learners completed written and spoken forms of productive vocabulary test (i.e., Lex30) as well as a story narrative task. Elicited speech samples were rated in terms of four aspects of L2 speaking proficiency (fluency, vocabulary, pronunciation, grammar), and the rating scores were compared with productive vocabulary scores. Results showed a significant correlation between the spoken and written vocabulary scores with a closer examination of the data indicating a gap between the two forms. Results of the vocabulary-speaking link indicated that spoken vocabulary knowledge was associated with all but one of the L2 speech ratings, while written vocabulary knowledge was not related to any of the rating scores. The current study provided methodological and practical implications with respect to the central role of modality in vocabulary testing.